Synergistically Induced Hypothermia and Enhanced Neuroprotection by Pharmacological and Physical Approaches in Stroke - Zhang, Jun (Aging Dis, 2018)
Hypothermia is considered as a promising neuroprotective treatment for ischemic stroke but with many limitations. To expand its clinical relevance, this study evaluated the combination of physical (ice pad) and pharmacological [transient receptor potential vanilloid channel 1 (TRPV1) receptor agonist, dihydrocapsaicin (DHC)] approaches for faster cooling and stronger neuroprotection. A total of 144 male Sprague Dawley rats were randomized to 7 groups: sham (n=16), stroke only (n=24), stroke with physical hypothermia at 31ºC for 3 h after the onset of reperfusion (n=24), high-dose DHC (H-DHC)(1.5 mg/kg, n=24), low-dose DHC (L-DHC)(0.5 mg/kg, n=32) with (n=8) or without (n=24) external body temperature control at ~38 ºC (L-DHC, 38 ºC), and combination therapy (L-DHC+ ice pad, n=24). Rats were subjected to middle cerebral artery occlusion (MCAO) for 2 h. Infarct volume, neurological deficits and apoptotic cell death were determined at 24 h after reperfusion. Expression of pro- and anti-apoptotic proteins was evaluated by Western blot. ATP and reactive oxygen species (ROS) were detected by biochemical assays at 6 and 24 h after reperfusion. Combination therapy of L-DHC and ice pad significantly improved every measured outcome compared to monotherapies. Combination therapy achieved hypothermia faster by 28.6% than ice pad, 350% than L-DHC and 200% than H-DHC alone. Combination therapy reduced (p<0.05) neurological deficits by 63% vs. 26% with L-DHC. No effect was observed when using ice pad or H-DHC alone. L-DHC and ice pad combination improved brain oxidative metabolism by reducing (p<0.05) ROS at 6 and 24 h after reperfusion and increasing ATP levels by 42.9% compared to 25% elevation with L-DHC alone. Finally, combination therapy decreased apoptotic cell death by 48.5% vs. 24.9% with L-DHC, associated with increased anti-apoptotic protein and reduced pro-apoptotic protein levels (p<0.001). Our study has demonstrated that combining physical and pharmacological hypothermia is a promising therapeutic approach in ischemic stroke, and warrants further translational investigations.